Cathepsin L of Sphaerospora molnari - localisation, function and diagnostic tools - Nechvile, Rudolf Lukas (Jihočeská univerzita, 2022)
The aim of this thesis was to develop diagnostic and quantitative assays/tools based on western blotting, confocal microscopy and immunogold electron microscopy, as well as flow cytometry, to determine the localisation and potential function of the highly expressed cathepsin L of the myxozoan parasite Sphaerospora molnari (SmolCL) in its fish host, the common carp. Furthermore, a recombinant SmolCL was used in a vaccine trial to estimate its potential for raising antibodies in carp and test their immunoprotective potential towards S. molnari. This thesis provides new methodological tools for research and allows a greater understanding of myxozoan parasite-fish host interactions based on proteolytic enzymes.
Cathepsin L of Sphaerospora molnari - localisation, function and diagnostic tools
Keywords: Sphaerospora molnari; Myxozoa; cathepsin L; carp; cnidarian parasite; cysteine protease; recombinant protein; polyclonal antibody; recombinant protease vaccine; western blot; flow cytometry; immunofluorescence microscopy; immunogold TEM; qPCR; ELISA; Sphaerospora molnari; Myxozoa; cathepsin L; carp; cnidarian parasite; cysteine protease; recombinant protein; polyclonal antibody; recombinant protease vaccine; western blot; flow cytometry; immunofluorescence microscopy; immunogold TEM; qPCR; ELISA